Comparative pharmacokinetic profile of cyclosporine (CsA) with a decapeptide and a linear analogue. Issue 12 (7th March 2017) - Price, David A.; Eng, Heather; Farley, Kathleen A.; Goetz, Gilles H.; Huang, Yong; Jiao, Zhaodong; Kalgutkar, Amit S.; Kablaoui, Natasha M.; Khunte, Bhagyashree; Liras, Spiros; Limberakis, Chris; Mathiowetz, Alan M.; et al.
Abstract : The synthesis and in vivo pharmacokinetic profile of an analogue of cyclosporine is disclosed. Abstract : The synthesis and in vivo pharmacokinetic profile of an analogue of cyclosporine is disclosed. An acyclic congener was also profiled in in vitro assays to compare cell permeability. The compounds possess similar calculated and measured molecular descriptors however have different behaviors in an RRCK assay to assess cell permeability.